Transcriptome Analysis of Newly Emerged Honeybees Exposure to Sublethal Carbendazim During Larval Stage - Wang, Kang; Fan, Rong-Li; Ji, Wen-Na; Zhang, Wen-Wen; Chen, Xiao-Mei; Wang, Shuang; Yin, Ling; Gao, Fu-Chao; Chen, Guo-Hong; Ji, Ting (Frontiers in Genetics, 2018)
There are increasing concerns regarding the impact of agrochemical pesticides on non-target organisms. Prior efforts indicated that pesticides could cause honeybee abnormal development in response to neurotoxins such as neonicotinoid. Here, we examined the influence of carbendazim, a widespread fungicide, on honeybee (Apis mellifera L.) brain development. Changes in global gene expression in the brains of newly emerged adult honeybees after carbendazim exposure during the larval stage, obtained from large-scale transcriptome approaches, revealed the molecular mechanisms responding to this fungicide in the honeybee brain. To further understand the effects of carbendazim on the health of honeybees, the functions of differentially expressed genes were assessed and compared. We found that neuroregulatory genes were repressed after carbendazim exposure, which at least partially accounts for the neurotoxic effects of this fungicide on honeybees. Moreover, carbendazim exposure also altered the expression of metabolism, transport, sensor, and hormone related genes. Notably, larvae in the carbendazim-treated group needed more time to shift into the dormant pupal state than larvae in the non-treated group. Accordingly, they possessed a low juvenile hormone and high ecdysone titers compared with control group, respectively. To our knowledge, the present study is the first reporting carbendazim neurotoxic effects, and that its sublethal effects may disturb honeybee development and weaken honeybee colonies.